The performative function of turmoil, trauma and tenacity in Judith 9–16: A speech act analysis - Hobyane, Risimati S. (HTS teologiese studies, 2023)
This article forms part of a larger project on the apocryphal Book of Judith. It explores the performative nature of turmoil, trauma and tenacity as found in the second half of the book (9–16). The impetus for this investigation is the work done by same author on chapters 1–8 of Judith while focusing on a similar theme. The present article suggests that the exploration of the turmoil, trauma and tenacity to be found in chapters 1–8 does not comprehensively represent all aspects that this topic has to offer to the reader of Judith. The contention here is that the theme of turmoil, trauma and the resultant tenacity in the second half of Judith needs further scholarly exploration as it reveals contrasting developments regarding two rivalling camps, that is, the Israelites and the Assyrians. From a speech act interpretive angle, the article asserts that turmoil, trauma and tenacity are intentionally utilised as a literary tool for indicating honour (Israelites) and shame (Assyrians). This has the potential to persuade the reader to make choices and/or decisions as they read the story.Contribution: The article is a continuation of my work on the first part of Judith (chapters 1–8), as indicated. Its main contribution rests on its unique approach to investigating the performative nature of trauma, turmoil and tenacity in the second part of the book, namely, chapters 9–16. The study of the theme of trauma, turmoil and tenacity in Judith is insightful and thought-provoking and does advance research around this fascinating book.